2020
DOI: 10.1002/cbf.3538
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates chronic intermittent hypoxia‐induced myocardial injury by modulating Ca2+ homeostasis

Abstract: Obstructive sleep apnea syndrome (OSAS) is an important consequence of chronic intermittent hypoxia (CIH). Astragaloside IV (AS‐IV) exerts multiple protective effects in diverse diseases. However, whether AS‐IV can attenuate CIH‐induced myocardial injury is unclear. In this study, rats exposed to CIH were established and treated with AS‐IV for 4 weeks. In vitro, H9C2 cardiomyocytes subjected to CIH exposure were treated with AS‐IV for 48 hours. Then the cardiac function, morphology, fibrosis, apoptosis and Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“… 2019 ; Jiang et al. 2020 ), this study indicated that CIH-exposed mice showed pathological changes and fibrosis, which were also risk factors for cardiac dysfunction. Hence, it is necessary to undertake active prevention and treatment in the early stage of CIH.…”
Section: Discussionmentioning
confidence: 62%
“… 2019 ; Jiang et al. 2020 ), this study indicated that CIH-exposed mice showed pathological changes and fibrosis, which were also risk factors for cardiac dysfunction. Hence, it is necessary to undertake active prevention and treatment in the early stage of CIH.…”
Section: Discussionmentioning
confidence: 62%
“…Capn1 −/− mice were also divided randomly into two groups ( n = 10): the control group (CK) and the chronic intermittent hypoxia group (MK). The model of CIH exposure established in this study was reported previously ( Jiang et al, 2020 ). Briefly, the mice were exposed to cages of automated, computer-controlled O 2 concentration exchange systems (Proox-100, Shanghai Tow-Int Tech Ltd.) to achieve a similar oxyhemoglobin saturation (SpO 2 ) nadir (50∼60%) in moderate to severe patients based on previous studies ( Zhou et al, 2014 ; Hu et al, 2021 ; Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Human coronary artery endothelial cells (HCAECs) were purchased from BLUEFBIO and grown in DMEM supplemented with 15% fetal bovine serum (HyClone, Logan, Utah, United States) in a CO 2 incubator as described previously ( Lv et al, 2019 ). The model of CIH in HCAECs was implemented by alternating cycles of 1% O 2 for 5 min followed by 20% O 2 for 5 min (3 cycles/h) at 37°C for 24 h in a chamber through automated, computer-controlled O 2 concentration exchange systems (GC-CT, Heilongjiang MAWORDE Industry and Trade Ltd.) as described previously ( Jiang et al, 2020 ; Xu H. et al, 2021 ; Yan et al, 2021 ). Cells were incubated with As-IV (100 µM), MDL-28170 (calpain-1 inhibitor, 20 µM) and SRT1720 (SIRT1 activator, 4 µM) for 48 h before CIH exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticoagulants and estrogen medications are currently commonly utilized to treat the condition [ 10 , 11 ], but their side effects, including renal failure, nausea, vomiting, dizziness, and exhaustion [ 12 ], are readily apparent. Recently, a number of natural compounds have demonstrated therapeutic potential for hypoxic illness [ 13 , 14 , 15 ]. They are easily accessible, have many physiological effects, and are non-toxic.…”
Section: Introductionmentioning
confidence: 99%